The hypostatic union – the foundation of the theandry of the Church - Petrov, George Daniel (Technium Social Sciences Journal, 2021)
God being love, He decided from ages the incarnation of Christ for the salvation of the whole mankind, which was subject to sin and death. In the Person of Christ, through the act of incarnation, performed at ”the fulness of time” (Galatians IV,4), the divine and the human nature are harmoniously completed, the latter becoming entirely obedient to the Father. If Christ had not been incarnated and if He had not lifted our own nature towards complete obedience to the Father, humanity would have never been able to obtain divine forgiveness and would not have known how to exist in the love of the Holy Trinity.